1978
DOI: 10.1111/j.1365-2605.1978.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyproterone Acetate (CPA) on Pituitary Gonadotrophin Release and on Androgen Secretion Before and After LH‐RH Double Stimulation Tests in Men

Abstract: CPA administration at a medium dosage of 10 mg daily for male fertility control resulted in reduced spermiograms and in a distinct decrease in basal T (70% reduction), DHT (50%), LH (30%) and FSH (40%). The episodic fluctuations in gonadotrophin secretion were not affected, but the spiking phenomenon of androgen secretion was completely abolished. Pituitary responses to LH‐RH were reduced significantly for both LH and FSH. Also the gradual increase of T and DHT in the course of the LH‐RH double stimulation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…These deleterious effects could be a result of inhibition of local effects of androgen on the testis due to decreased androgen production and or competitive inhibition of androgens a t the receptor level. Adverse effects of CPA on testes were reported earlier in primates (Michael et al, 1972;Petry et al, 1972;Morse et al, 1973;Koch et al, 1976;Neumann and Schenk, 1976;Roy et al, 1976;Moltz et al, 1978;Roy and Chatterjee, 1979). The presence of metachromatically staining lipids in the Sertoli cell cytoplasm after CPA treatment could be due to quiescent spermatogenesis as reported for normal monkeys during the summer months (Sehgal et al, 1986).…”
Section: Discussionsupporting
confidence: 52%
“…These deleterious effects could be a result of inhibition of local effects of androgen on the testis due to decreased androgen production and or competitive inhibition of androgens a t the receptor level. Adverse effects of CPA on testes were reported earlier in primates (Michael et al, 1972;Petry et al, 1972;Morse et al, 1973;Koch et al, 1976;Neumann and Schenk, 1976;Roy et al, 1976;Moltz et al, 1978;Roy and Chatterjee, 1979). The presence of metachromatically staining lipids in the Sertoli cell cytoplasm after CPA treatment could be due to quiescent spermatogenesis as reported for normal monkeys during the summer months (Sehgal et al, 1986).…”
Section: Discussionsupporting
confidence: 52%
“…At a dose of 30 mg/day it decreases testosterone levels to extremely low values, reducing sperm count and motility. Even a 12 weeks treatment with as low a dose as 10 mg of cyproterone acetate decreases plasma LH, FSH, T and DHT levels (Moltz et al 1978). At this dose it reduces the sperm count as well as motility, and at higher doses ( 100 mg/day) it renders spermatozoa immotile.…”
Section: Antiandrogensmentioning
confidence: 97%
“…As to the antiandrogens, cyp-oterone acetate is a highly potent progestative, inhibiting gonadotrophin secretion, with a high affinity for the androgen receptor and inhibiting 5a-reductase activity (Petry et al 1972;Moltz et al 1978). At a dose of 30 mg/day it decreases testosterone levels to extremely low values, reducing sperm count and motility.…”
Section: Antiandrogensmentioning
confidence: 99%
“…The central effects of antiandrogens on the adenohypophysis were believed to result from the progestational activity of these compounds [3, 161. Physiological and biochemical studies dealing with the effects of cyproterone acetate on gonadotropin secretion showed vaned results. Some investigators reported normal serum and urinary concentrations of gonadotropins [5, 181, while others showed a decrease in LH and FSH [6,10,13,191. Measurement of growth hormone secretion did not indicate any significant alterations following cyproterone acetate therapy [9, 101. Morphological studies conducted at the light microscopic level showed an increase in the number of somatotrophs, atrophy of FSH cells, and hypertrophy of LH cells [7, 81.…”
Section: Introductionmentioning
confidence: 99%
“…The pituitary gland has been implicated as a target organ by workers studying the central effects of the antiandrogen cyproterone acetate [13,14,16,191. The central effects of antiandrogens on the adenohypophysis were believed to result from the progestational activity of these compounds [3, 161. Physiological and biochemical studies dealing with the effects of cyproterone acetate on gonadotropin secretion showed vaned results.…”
Section: Introductionmentioning
confidence: 99%